Association between elevated serum REG Iα levels and eGFR decline in patients with chronic kidney disease: a cross-sectional study in eastern China - Ling Li; Hui Wang; Sheng Chen; Xi Huang; Bin Wang; Nan Huang; Rolf Graf; Xiaodong Wu; Xiangyun Zhu; Zhiyi Shu; Xiuxiu Hu; Jinfang Sun; et al. (BMJ Open)
Objectives This study aimed to investigate the relationship between serum regenerating protein Iα (REG Iα) levels and estimated glomerular filtration rate (eGFR) and to evaluate the diagnostic efficiency of REG Iα in chronic kidney disease (CKD).Design This is a cross-sectional study.Setting The study was conducted in eastern China between August 2022 and August 2023.Participants A total of 880 participants aged over 18 years were enrolled, with 220 non-CKD participants (111 males, 50.45%) and 660 patients with CKD (366 males, 55.45%). CKD was diagnosed based on the Kidney Disease: Improving Global Outcomes (KDIGO) 2012 guidelines. Exclusion criteria included participation in other trials, acute kidney injury, end-stage kidney disease undergoing renal replacement therapy, pregnancy, active infections, gastrointestinal or pancreatic inflammation, history of gastrointestinal or pancreatic resections, cancer and mental disorders.Results Serum REG Iα was significantly higher in the CKD group (125.54 (60.28–303.39) ng/mL) compared with those in the non-CKD group (24.62 (14.09–37.32) ng/mL, p<0.001). Positive correlations were observed between serum REG Iα and serum creatinine, cystatin C (Cys-C), and kidney injury molecule 1 (KIM-1), while a negative correlation was identified with eGFR. After adjusting for sex, diabetes, hypertension and fasting blood glucose, the multivariate regression analysis demonstrated a significant association between serum REG Iα and eGFR (OR=1.737 (1.263–2.388), p=0.001). Furthermore, serum REG Iα levels increased progressively with declining kidney function categorised by eGFR (p<0.001). In CKD screening, serum REG Iα demonstrated strong diagnostic performance, with an area under the receiver operating characteristic curves (AUC) of 0.860 (0.813–0.899), providing a sensitivity of 71.63%, a specificity of 86.89%, a positive predictive value of 94.30% and a negative predictive value of 46.85%. Additionally, serum REG Iα exhibited an AUC of 0.769 (0.712–0.819) for identifying high- and very-high-risk CKD based on KDIGO risk stratification. Its sensitivity significantly outperformed serum Cys-C and KIM-1 (82.80% vs 75.16% and 36.94%, respectively).Conclusions This study provided compelling evidence that serum REG Iα levels were notably elevated in patients with CKD and closely associated with kidney function. REG Iα may serve as a promising biomarker for CKD detection and risk stratification.Clinical trial registration The study was approved by the Ethics Committee of Zhongda Hospital (approval number: 2022ZDSYLL204-P01) and conducted in compliance with the Helsinki Declaration. The clinical trial was registered under ChiCTR2300072247.